Neglect dyslexia as a word-centred impairment: A single case study - Moore, M; Demeyere, N (Elsevier, 2018)
Neglect Dyslexia is a neuropsychological syndrome in which patients commit consistently lateralised letter omission, addition, and substitution errors when reading individual words. Although neglect dyslexia frequently co-occurs with domain-general visuospatial neglect, some cases of neglect dyslexia may be best characterised as a dissociable impairment within a word-centred reference frame. This investigation employs data from a single case study of a patient who demonstrated word-centred neglect dyslexia to clarify neglect dyslexia's relationship with visuospatial neglect. AB completed the Oxford Cognitive Screen and an original reading assessment in which she read 302 words, pseudo-words, and numbers presented in normal, vertical, and mirror-reflected orientations. AB was found to commit consistently lateralised right neglect dyslexia errors (e.g., SHOWN misread as "show" or RELATED misread as "relate"). By contrast, AB did not exhibit object-centred or viewer-centred neglect. AB was also found to commit lateralised reading errors affecting the terminal portions of words when lateralised spatial bias was eliminated by presenting words vertically. Additionally, AB consistently misread terminal letters (originally right-lateralised) even when words were mirror-reflected so that these letters were presented in the left side of space. AB committed no neglect dyslexia errors when reading normally, vertically, or mirror-reflected numbers, and demonstrated a qualitatively different error pattern when reading pseudo-words. The results of this case study imply that neglect dyslexia can involve a content-specific, word-centred cognitive deficit and can be dissociated from egocentric and allocentric visuospatial neglect.